Dampak Penggunaan Anotasi Penamaan yang Berbeda pada Kinerja NER - Saputra, I Made Widi Arsa Ari; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
In developing the NER model, naming annotations are used as an important part of the training process.  The  impact  of  using  different  naming  annotations  on  NER  performance  has  been  a concern in the research community. So,the writer wants to once again, test the impact of using different  naming  annotations  using  the  spaCy  library  on  English  documents.  Using  2  naming schemes namely BIO and IOBES, using the spaCy model to get 0.96 accuracy for BIO and 0.95 for IOBES.